MELARIKAN ANAK KE LUAR NEGARA: KAWALAN UNDANG-UNDANG DI MALAYSIA DAN DI BAWAH THE HAGUE CONVENTION ON THE CIVIL ASPECTS OF INTERNATIONAL CHILD ABDUCTION 1980 - Noor, Zanariah (Jurnal Syariah, 2010)
The issue of international child abduction arose when non-custodial parents abduct their own children and brought them to their own countries. Since Malaysia is not a signatory-state to the Hague Convention on The Civil Aspects of International Child Abduction 1980, which facilitates the returning of children to their habitual residence, efforts to bringing back the children to Malaysian jurisdiction or foreign jurisdiction has been facing difficulties and has caused trauma to both conflicting parents as well as the children. This article focuses on the aspects of which will be considered by Malaysian and foreign court with regards to international child abduction cases involving the Muslims.